Analysis of Instructional Imperatives in Genshin Impact for EFL Vocabulary Acquisition. - Priyanto, Amalina Zulfah; Kalisa, Pasca (Journal of English Language and Education, 2026)
Digital games are increasingly recognized as supplementary sources of language input in English as a Foreign Language (EFL) contexts because they provide interactive and context-rich language use. However, previous studies have mainly focused on game mechanics or learner motivation, while linguistic features of in-game instructional texts remain underexplored. This study examines the types and functions of imperative constructions in Genshin Impact and their potential as linguistic input for incidental EFL vocabulary acquisition. A total of 93 English instructional texts were collected from the primary quest “The Forgotten Thief” during approximately 120 minutes of gameplay. Using a descriptive qualitative design with content analysis, the data included dialogue-based instructions, tutorial prompts, and quest objectives. The findings show that simple and inclusive imperatives are most frequent, followed by compound, negative, courteous, and idiomatic forms. These imperatives provide repeated exposure to functional language, suggesting their potential to support EFL learners’ vocabulary development and pragmatic awareness.